Residual DDTs and Fatty Acid Compositions in Popular Two Sea Fish Samples (Dhaka University Journal of Science, 2017)
Fatty acid compositions, DDT and its metabolites of popular two sea fishes i.e., Pampus argenteus (Pomfret) and Lates calcarifer (Vernacular) were determined. Lipid was extracted by ethylacetate, saponified and converted to methyl ester using BF3-MeOH to determine fatty acid compositions by GC-FID.For DDTs,edible parts of the fish samples were extracted by solid phase dispersion method, cleaned up with concentrated H2SO4 and finally analyzed by GC-ECD. The LOD and LOQ for DDE, DDD, 2, 4´-DDT and 4, 4´-DDT were found to be 0.39, 0.39, 1.56, 1.56 and 1.36, 1.36, 4.89 and 4.89 μg/kg respectively. Internal Standard CB53 (0.25mg/g) was used to determine the recovery of the experiment and was within range of 77.48-92.35 %. The residual amount of DDT (2, 4´-DDT+4, 4´-DDT), DDE and DDD in pomfret and vernacular were found to be in the range of 13.56-81.05, 3.86-21.08, 4.32-35.4, and 23.44-85.59, 2.90-5.81 and 6.33-12.44 μg/kg respectively. The ratios of DDT/ΣDDTs in pomfret and vernacular were 0.675 and 0.773 respectively. Among the saturated fatty acids, palmitic acid was predominant (62.84% for pomfret and 41.81% for vernacular) whereas among the unsaturated fatty acids oleic acid was predominate and higher in pomfret (15.11 %).Dhaka Univ. J. Sci. 65(1): 77-80, 2017 (January)